Toward an integrated understanding of how extreme polar light regimes, hybridization, and light-sensitive microbes shape global biodiversity - Saikkonen, Kari; Birge, Traci; Fuchs, Benjamin; Helander, Marjo; Ihalainen, Janne A.; Nissinen, Riitta; Puigbò, Pere (CELL PRESS, 2025)
Low knowledge sharing across disciplines studying geo-evolutionary processes determining species adaptations hinders the mitigation of biodiversity loss driven by human-induced climate warming. Further, the impacts of microbes and light regimes on species adaptations to accelerated climate warming are largely ignored. On a geologic timescale, range shifts to higher latitudes necessitate adaptation to new light environments, including extreme polar seasons, i.e., "polar night." Chemical crosstalk among coevolving microbes and plants modulates ecologically relevant traits, and photosensitive and other microbes may aid plant adaptation. We hypothesize that hybridization in new "circumpolar hybrid zones"and plant-microbial cooperation in those zones and elsewhere will be significant in maintaining genetic admixture and species diversity on a geological timescale. We propose the concept of circumpolar hybrid zones and an integrated framework, inclusive of microbes, to unite disparate research disciplines, advance understanding of evolution, and improve strategies for climate adaptation and mitigation.